Nerve conduction studies of ulnar and median nerves in elite rowers - Colak, S.; Bamac, B.; Mulayimc, S.; Dincer, O.; Colak, T.; Selekler, H. M.; Turker, M.; Colak, E.; Ozbek, A.; Sivri, I. (Journal of the Anatomical Society of India, 2018)
Introduction: Rowing is a strenuous sport that demands high levels of training, strength and repetitive motion. This study was conducted for assessing the impact of rowing act on the ulnar and median nerves which crosses the wrist area in elite rowers. Method: Twenty asymptomatic professional male rowers and 20 non-active males were evaluated in this study. The neuro-physiologic evaluation comprised sensory and motor nerve conductions of median and ulnar nerves. Result: The sensory conduction velocity of the ulnar and median nerves were noticably delayed in both extremities of rowers when they were compared with control group. There weren`t any statistical differences in motor conduction velocities of ulnar and median nerves between the control group and rowers in not only dominant but also non-dominant extremities. Discussion: In conclusion, the abnormal median and ulnar sensory nerve conduction at the wrist region might show a subclinical entrapment neuropathy as a result of arduous wrist moves in rowers.